2021
DOI: 10.2147/vhrm.s339769
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Cardio-Ankle Vascular Index as a Predictor of Mortality in Patients on Maintenance Hemodialysis

Abstract: Aim Mortality rate of maintenance hemodialysis patients is known to be high. Cardio-ankle vascular index (CAVI) is an index reflecting the proper stiffness of the arterial tree from the origin of the aorta to the ankle. We aimed to clarify the utility of CAVI as a predictor of mortality in hemodialysis patients. The roles of age and nutritional conditions on survival were also examined. Methods We followed 242 patients undergoing hemodialysis for 6 consecutive years. Da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…Specifically, predictive performance of haPWV for renal function decline was lower compared with CAVI, despite many individuals with high haPWV showed relatively increased BP at the time of measurement. This result is consistent with our previous study showing that CAVI was more strongly associated than haPWV with mortality in hemodialysis patients [28]. The relatively weak predictive performance of haPWV for renal function decline compared with CAVI may be because of the underestimation of atherogenic risk factors other than elevated BP.…”
Section: Discussionsupporting
confidence: 92%
“…Specifically, predictive performance of haPWV for renal function decline was lower compared with CAVI, despite many individuals with high haPWV showed relatively increased BP at the time of measurement. This result is consistent with our previous study showing that CAVI was more strongly associated than haPWV with mortality in hemodialysis patients [28]. The relatively weak predictive performance of haPWV for renal function decline compared with CAVI may be because of the underestimation of atherogenic risk factors other than elevated BP.…”
Section: Discussionsupporting
confidence: 92%
“…In this study, we found that CAVI increases in HIV patients treated with cART, but is similar among cART-naïve HIV patients and non-HIV controls. CAVI is a sensitive marker of arterial stiffness and several studies have shown that it predicts CVD in patients and the general population [ 9 , 10 ]. From our literature search, we found just two studies that reported CAVI in HIV patients.…”
Section: Discussionmentioning
confidence: 99%
“…This makes CAVI unique from other arterial stiffness that is based on pulse wave velocity (PWV), such as carotid-femoral PWV and brachial-ankle PWV [ 6 , 7 ]. CAVI has been reported in several studies to be associated with cardiovascular-related organ damage [ 8 , 9 ] and mortality [ 10 ]. Several studies conducted in Africa and other parts of the world have reported arterial stiffness in HIV patients using PWV [ 2 , 11–14 ].…”
Section: Introductionmentioning
confidence: 99%
“…We have previously conducted a longitudinal study comparing CAVI with haPWV, an index incorporated into the CAVI structural equation including central and peripheral arteries. 19 Of the 209 hemodialysis patients, 38 died for 6 years. Resultantly, in the Cox-proportional hazards analyses, 1 SD increase in both parameters contributed almost equally to allcause mortality [CAVI: hazards ratio (HR) 1.595, haPWV: HR 1.695].…”
Section: Comparison Of Cavi and Pwvmentioning
confidence: 99%